Modifiable factors which predict children's gross motor competence: a prospective cohort study - Lisa M. Barnett; Jill A. Hnatiuk; Jo Salmon; Kylie D. Hesketh (BMC, 2019)
Abstract Background Fundamental motor skills (FMS) are important for physical activity and healthy weight status in children, yet it is unclear which early childhood factors facilitate subsequent motor skill. The aim of this prospective study was to investigate which modifiable family and home environment factors in the early years predict children's FMS at age five. Methods Mothers from the Melbourne InFANT program (registered with the International Standard Randomised Controlled Trial Number Register (ISRCTN81847050)) completed questionnaires when child was aged 4, 9, 19 months old, and 3.5 years old on factors hypothesised to predict motor skills. Some factors were grouped in tertiles (high, medium, low) due to the nature of the distribution. At 5 years old children were assessed on 6 locomotor and 6 object control skills (Test of Gross Motor Development-2). Eight regression models examined the association between factors at each time-point and children's skills (object control and locomotor) at 5 years old. Results The sample varied by time-point (178 to 259 children). Maternal physical activity optimism (4 months; β = 2.43), home physical activity equipment (9 months; β = 0.82), time outdoors - middle (9 months; β = 2.50) and highest tertile (9 months; β = 2.86), time free to move about - highest tertile (19 months; β = 2.41), time with older children - middle (19 months; β = 3.15) and highest tertile (3.5 years; β = 3.00) were predictive of better locomotor scores. Mothers' own physical activity (9 months; β = − 0.01) and time active with mum - highest tertile (3.5 years; β = − 3.73) were negatively associated with locomotor skill. Time with older children - highest (4 months; β = 2.27) and middle tertile (19 months; β = 2.97), time free to move about - middle (19 months; β = 2.55) and highest tertile (19 months; β = 2.47), and more home equipment (9 months; β = 0.83); (3.5 years; β = 0.17) were predictive of better object control skills. Maternal physical activity knowledge (3.5 years; β = − 3.05) was negatively associated with object control skill. Conclusions Providing a supportive environment with older children and equipment, and allowing toddlers' freedom to move, appears important. Opportunities exist to educate parents on their important role in developing children's motor skills. Clinicians could advise parents that the home environment can make a difference to their child's FMS starting from infancy.